INCREASING SALES OF BAE-BAE RICE BOWL UMKM - Swastika, Yuan; Abdilah Rabbani, Inayah; Sofian Maksar, Muhammad (Jurnal Pengabdian Masyarakat Berkarya, 2024)
This community service is entitled Increasing Sales at Bae-Bae Rice Bowl Micro Small and Medium Enterprises. This community service activity is part of the learning process which aims to provide direct experience outside of the world of work. This research aims to evaluate the implementation of the community service program at Bae Bae Rice Bowl, a Micro Small Medium Enterprise engaged in Food and Beverage in Kendari. This service program is focused on activating Tiktok social media accounts with promotional content to improve brand positioning, sales, and build reputation. The results of Community Service show that the service program at Bae Bae Rice Bowl has successfully reactivated the Tiktok account with an effective content strategy. The result is increased social media engagement and product sales, as well as improved brand positioning and consumer trust.